Kinetin modulates physio-hormonal attributes and isoflavone contents of Soybean grown under salinity stress - Hamayun, Muhammad; Hussain, Anwar; Khan, Sumera Afzal; Irshad, Muhammad; Khan, Abdul Latif; Waqas, Muhammad; Shahzad, Raheem; Iqbal, Amjad; Ullah, Nazif; Rehman, Gauhar; Kim, Ho-Youn; Lee, In-Jung (Frontiers in Plant Science, 2015)
Crop productivity continues to decline due to a wide array of biotic and abiotic stresses. Salinity is one of the worst abiotic stresses, as it causes huge losses to crop yield each year. Kinetin has been reported as plant growth regulator since long, but its role in improving plant growth and food quality under saline conditions through mediating phytohormonal cross-talk is poorly studied. Current study was designed to evaluate the impact of exogenously applied kinetin on growth, isoflovones and endogenous phytohormones of soybean grown under NaCl induced salt stress. Soybean plants were grown in perlite (semi hydroponic), and under controlled green-house conditions. Elevated levels of exogenous kinetin significantly mitigated the adverse effect of NaCl and rescued plant growth attributes i.e. plant height, fresh and dry biomass of soybean plants grown in all treatments. Higher diadzen, glycitin and genistin contents were observed in plants treated with elevated kinetin in the presence or absence of NaCl induce salt stress. The gibberellins (GAs) biosynthesis pathway was up-regulated by kinetin as the bioactive GA1 and GA4 contents were significantly higher in kinetin treated plants, as compared to control, while GAs level reduced in NaCl treated plants. Contrary to gibberellins, the abscisic acid contents declined with kinetin but promoted in NaCl stressed soybean plants. The endogenous jasmonic acid and salicylic acid contents of soybean enhanced with elevated kinetin application, but they showed an antagonistic response under salt stress. Current study supports the active role of kinetin to ameliorate the adverse effects of salt stress on the growth and food quality of soybean. The favourable role of kinetin towards soybean growth under salt stress may be attributed to its potential to modulate cross-talk between the various phytohormones involved in soybean growth and its resistance to salinity stress.